Lifting Divisors on a Generic Chain of Loops. Issue 2 (1st June 2015) - Cartwright, Dustin; Jensen, David; Payne, Sam
Abstract: Let C be a curve over a complete valued field having an infinite residue field and whose skeleton is a chain of loops with generic edge lengths. We prove that any divisor on the chain of loops that is rational over the value group lifts to a divisor of the same rank on C, confirming a conjecture of Cools, Draisma, Robeva, and the third author.